Sustainable Tourism as a Development Strategy in Indonesia - Fadli, Moh.; Susilo, Edi; Puspitawati, Dhiana; Ridjal, Abraham Mohammad; Maharani, Diah Pawestri; Liemanto, Airin (Journal of Indonesian Tourism and Development Studies, 2022)
In recent years, Indonesia has increasingly shown its dependence on the tourism sector by adopting the idea of sustainable tourism as a development strategy. Based on doctrinal legal research method with a statutory and conceptual approach, this article used the concept of sustainable tourism to explore the opportunities and challenges faced by Indonesia in developing tourism sector. This article argues that even though Indonesia has the 2009 Tourism Law that specifically regulates tourism governance based on a multisectoral approach, this law does not clearly adopt the concept of sustainable tourism, resulting in different perceptions between actors at various levels of tourism administration. The sustainable tourism agenda in particular still depends on the initiatives of each actor, is fragmented and heavily influenced by various factors of power relations, financial capacity, and human resources. This article suggests the need for strengthening legal and institutional frameworks to achieve the 2030 Agenda for Sustainable Development Goals that place communities as the subject of tourism development.Keywords: Sustainable tourism, the 2009 Tourism Law, the 2030 Agenda for Sustainable Development Goals, tourism governance.